(untitled) (UKLO Proceedings, 2026)
Introduction: This paper addresses the critical reevaluation of cultural diplomacy’s role in 21st-century international relations. In an era where the effectiveness of soft power tools is often questioned, this study aims to explore a novel methodological approach by examining the intersection of archaeological heritage and cultural diplomacy to foster sustainable development in global affairs. Methods: The research employs a qualitative analysis of existing literature and specific case studies in the field of heritage diplomacy. It examines the mechanisms through which archaeological sites, artefacts, and cultural narratives are integrated into diplomatic strategies to promote intercultural dialogue and sustainable practices. Results: The analysis demonstrates that archaeological heritage, due to its profound impact on identity formation and cultural narratives, functions as a crucial component of the "software" of modern societies. The findings indicate its significant potential as a soft power tool to enhance international relations by contributing to peacebuilding, preserving cultural diversity, stimulating responsible tourism, and supporting economic growth through heritage preservation. Discussion: The study concludes that integrating archaeological heritage with cultural diplomacy strategies offers a powerful means to advance Sustainable Development Goals (SDGs) while strengthening political and economic ties. The results underscore the broader applicability of heritage diplomacy in global peace and cooperation efforts. The paper also discusses the inherent challenges of leveraging complex cultural elements and suggests areas for further research into the practical implementation of these interdisciplinary strategies.